GAMBARAN PENGETAHUAN IBU HAMIL TENTANG PEMANFAATAN BUKU KIA DI KLINIK UTAMA AYAH BUNDA PANGKALAN KERINCI TAHUN 2018 - Uswantun Chasanah (Jurnal Kesehatan Husada Gemilang, 2019)
Poor awareness of the society on health of pregnant women becomes main factor of high degree of Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) in Indonesia. One of the efforts to reduce MMR and IMR is to create conditions during pregnancy, childbirth and childbirth safe and monitored by health workers. Therefore, the Ministry of Health publishes the MCH Handbook to increase maternal awareness and behavior on the importance of health through the use of the MCH Handbook. Granting many factors to be aware, one of the death factors is the ignorance of pregnant women and family on pregnancy; so the government attempts to improve the women’s awareness and knowledge about the benefits of the MCH Handbook. This study aims at recognizing the portrait of the pregnant women’s knowledge on the use of MCH Handbook at Main Clinic of Ayah Bunda Pangkalan Kerinci in 2018. The type of the research is descriptive. The research subjects were 96 pregnant women at Main Clinic of Ayah Bunda Pangkalan Kerinci, which were taken by accidental sampling. Data collection was using questionnaire which was distributed to the pregnant women. The results clarify that there are 54.2% of pregnant women with good knowledge, 28.1% of pregnant women with sufficient knowledge, and 17.7% of pregnant women with poor knowledge. The pregnant women who use MCH Handbook are 49% and who do not are 51%. Great knowledge does not affect mothers’ understanding on the obtained information about the benefits of MCH Handbook, so they do not use it properly. The researcher extremely suggests that the health workers provide information to pregnant women about the use of MCH Handbook, so they consider the benefits of it for them and their children up to 6 years old.